The relationship between commodity types, spatial characteristics, and distance optimality of logistics facilities - Sakai, Takanori; Kawamura, Kazuya; Hyodo, Tetsuro (Journal of Transport and Land Use, 2018)
We analyze the relationship between the location of logistics facilities and the goods vehicle travel distances for the shipments associated with the facilities, using data from a large urban freight survey conducted in the Tokyo Metropolitan Area in 2013. Our analysis categorizes the logistics facilities into groups based on the type of commodity they handle. The analysis sheds light on the complex relationship between the location and “distance optimality gap,” defined as the gap between the minimum travel distance possible and the actual distance traveled by goods vehicles. The results indicate that, while the lack of available space for logistics land use near the urban center leads to significant distance optimality gaps for some logistics facility groups, such as those handling daily goods, these same locations may not be advantageous for others. Also, the logistics facilities in the exurbs are likely to have large distance optimality gaps because these locations are often far away from the origins and destinations of their shipments. In terms of land-use policy, the study reveals that simply concentrating logistics facilities near the urban core or suburbs may not reduce truck traffic. Detailed data on logistics facilities and shipments are crucial for formulating effective approaches to improve the distance optimality of logistics land use.